Analysis of Decreased Public Awareness in the Application of Health Protocols with the C4.5 . Algorithm - Arfika, Retno; Safii, M. (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2021)
The purpose of this study is to determine the dominant factors that affect the decline in public awarenesson the application of health protocols using the C4.5 Algorithm. Sources of data used in this study obtained by conducting observations and interviews. The variables used include (1) Employment, (2) Environment, (3) Sanctions and (4) Concern. The research test process uses RapidMiner software to create a decision tree. The results obtained 6 rules with 4 rules decreasing status and 2 rules increasing status. The level of accuracy obtained is 100%. The results of this study are expected to be input for the surrounding community to better understand the importance of implementing health protocols at this time, so that they can help the Government to succeed in the health protocol awareness program in inhibiting the spread of Covid-19 in Indonesia.